Analysis of propulsion performance of wave-propelled mechanism based on fluid-rigid body coupled model. (August 2022) - Chang, Zongyu; Feng, Zhanxia; Deng, Chao; Zhao, Lin; Zhang, Jiakun; Zheng, Zhongqiang; Yu, Zhenjiang
Wave-propelled mechanisms are applied to propel unmanned marine vehicles such as Wave Glider and wave-powered boats, which can convert wave energy directly into propulsion. In this paper, a fluid-rigid body coupled dynamic model is utilized to investigate the propulsion performance of the wave-propelled mechanism. Firstly, the coupled dynamic model of the wave-propelled mechanism is developed based on relative motion principle by combining rigid body dynamics model and CFD method. Then, the motion responses of wave-propelled mechanism are calculated. The relationship between the propulsion force, heave and pitch motion of hydrofoil are analyzed by using phase diagrams and the actual operation conditions of propulsion mechanism are obtained. Besides, the effects of restoring spring stiffness and wave heights on the propulsion performance are also investigated, and the vortex evolution is illustrated at different moments of movement and different restoring stiffness. These works can be helpful for the design and optimization of different kinds of wave-propelled vehicles.